NUCLEAR DATA V&V ANALYSIS FOR FUSION APPLICATIONS: INTEGRAL BENCHMARKS AND DECAY DATA - Vilkhivskaya Olga; Gilbert Mark (EPJ Web of Conferences, 2021)
A reliable estimation of the operational parameters is one of the primary concerns in the design of magnetic fusion devices such as ITER and DEMO. Methods of diagnostics and control over the critical plasma parameters determining its stability and efficiency rely on the high-energy neutron field monitoring. Extreme operational environment, such as high-energy neutron flux, electromagnetic radiation, and high temperatures might reduce the performance of the detector systems. Therefore, research and development activities in detector prototyping are carried out to address this problem. To predict the performance of the detector materials, simulations using the latest releases of the nuclear data libraries as input for the inventory codes are carried out. This paper describes the latest validation and verification (V&V) benchmark exercise for FISPACT-II & TENDL-2017 based on the fusion decay heat measurements performed at the Japanese FNS facility for the materials in the diagnostic components for the radiation measurements. The breakdown of decay-heat contributions from individual radionuclides have been employed to interpret the simulated results, benchmark the data against the experimental measurements, and revise the neutron-induced reactions cross-section and decay data for the associated radionuclides for the upcoming release of the TENDL-2019 nuclear data library.